Beyond the classroom: Fostering English communication skills in vocational education through podcasting and radio broadcasting - Hamid, Syifa Fadhilah; Forsia, Lastry; Isnaniah, Isnaniah (Universitas Islam Malang, 2024)
Addressing the challenge of developing effective English communication skills in vocational education, this study explores the integration of podcasting and radio broadcasting as an alternative to traditional classrooms. The goal is to provide vocational students with a more immersive and practical learning experience in line with communicative language teaching principles. Putra Rifara Vocational School initiated a Radio Podcast program, emphasizing technological proficiency. A seminar,